2021
DOI: 10.1159/000517262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <b><i>Helicobacter pylori</i></b> Genotypes in Obese Patients with Gastric Ulcer, Duodenal Ulcer, and Gastric Cancer: An Observational Study

Abstract: <b><i>Introduction:</i></b> Obesity is a well-known risk factor for a variety of gastrointestinal disorders (GID). <i>Helicobacter pylori</i> is associated with different GID, such as gastric cancer and chronic gastritis. In this study, we investigated the prevalence of dominant genotypes in <i>H</i>. <i>pylori</i> isolated from obese patients diagnosed with gastric ulcer, duodenal ulcer, and gastric cancer. <b><i>Methods:</i></b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A recent observational study revealed a high prevalence of vacA and cagE followed by cagA , dupA , iceA1 , oipA , and babA2 genotypes in H. pylori strains isolated from obese patients diagnosed with gastric ulcer, duodenal ulcer, and gastric cancer. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent observational study revealed a high prevalence of vacA and cagE followed by cagA , dupA , iceA1 , oipA , and babA2 genotypes in H. pylori strains isolated from obese patients diagnosed with gastric ulcer, duodenal ulcer, and gastric cancer. 38 …”
Section: Discussionmentioning
confidence: 99%
“…A recent observational study revealed a high prevalence of vacA and cagE followed by cagA, dupA, iceA1, oipA, and babA2 genotypes in H. pylori strains isolated from obese patients diagnosed with gastric ulcer, duodenal ulcer, and gastric cancer. 38 Moderate consumption of the 'refined grains' food group, characterized by breads, cakes, cookies, and breakfast cereal, was positively associated with H. pylori infection. These foods are rich in carbohydrates with a high glycemic index and are present in the diet of Brazilians.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 98%
“…These cells feature a strong affinity for deamidated gluten-derived peptides, which bind and present to CD4 T cells in suburothelium, starting up the inflammatory cascade, which is a function of CD. Auto-antibodies against TG2, specifically anti-TG2 and anti- EMA, are responsible for the deamination of gluten in CD patients [ 22 , 23 ] . However, the most important alteration is intestinal damage, often characterized by villous atrophy, a scientific feature in most CD cases.…”
Section: Introductionmentioning
confidence: 99%
“…The spiral‐shaped bacterium has 3–5 polar flagella that are utilized for locomotion and is positive for the urease, catalase, and oxidase enzymes 2 . Most H. pylori strains express virulence factors that have evolved it interfere with host cell signalling pathways, this remarkable ability to persist for decades in the harsh stomach environments, primarily because the host cannot effectively eliminate it 3,4 . By utilizing urease to convert urea into ammonia, H. pylori has acquired the ability to thrive in the extremely acidic environment, setting it apart from other viruses and bacteria 5 .…”
Section: Introductionmentioning
confidence: 99%